KORELASI ANTARA GERIATRIC NUTRITIONAL RISK INDEX DENGAN LAMA RAWAT PASIEN GERIATRI DI RUMAH SAKIT SANGLAH, DENPASAR - Andriyasa, K; Kuswardhani, RA Tuty; Aryana, IGP Suka; Astika, N; Putrawan, IB (journal of internal medicine, 2012)
Patients at risk of malnutrition are associated with a poor outcome. There are several tools that we can use to assess the nutritional status. European Society of Parenteral and Enteral Nutrition (ESPEN) guidelines and the French Program National Nutrition Sante (PNNS) recommend Mini Nutritional Assessment (MNA) to detect the risk of under nutrition among elderly subjects. The MNA which based on a Questionnaire does not use biological indicators. It is more adapted to the elderly at home or nursing home setting than hospitalization. We want to evaluate the new tool Geriatric Nutritional Risk Index (GNRI) that more simple than MNA to assess nutritional status and predict hospitalization outcomes in geriatric patients. This is a cohort study to evaluated correlation between GNRI score with length of stay in elderly patients. We evaluated nutritional status using Geriatric Nutritional Risk Index (GNRI) and Mini Nutritional Assessment (MNA) for elderly patients that admitted in Sanglah Hospital (Internal Department, class III) between February 2010 and April 2010. The patients were nutritionally assessed within 48 hours of hospital admission and studied in correlation to length of stay and in-hospital mortality. Fifty complete assessments were available for analysis. There are 32 male (62%) and 18 female (38%) with mean age are 67.2 (60 ? 82) years old. GNRI score and MNA correlated inversely with length of stay in elderly patients (r = -0.67; p < 0.000) and (r = -0.44; p = 0.004) respectively. There are three fatal outcome (death) and all of cases with GNRI score grade 4 (major risk, GNRI score < 82) . GNRI score has a significant correlation with MNA score (r = 0.72; p < 0.000). In conclusion: Poor nutritional status as measured by GNRI was associated with a longer length of stay and increased inhospital mortality. GNRI is a simple tool and has more significant correlation with hospitalization outcomes than MNA.
Keywords: GNRI, MNA, hospitalization outcome